Respuesta :
Answer: The correct option is C, i.e., x=3 and x=-7.
Explanation:
The given equation is,
[tex]log_4(x)+log_4(x-3)=log_4(-7x+21)[/tex]
Using product property of logarithm [tex]log_a(mn)=log_am+log_an[/tex]
[tex]log_4(x(x-3))=log_4(-7x+21)[/tex]
[tex]log_4(x^2-3x)=log_4(-7x+21)[/tex]
On comparing both sides,
[tex]x^2-3x=-7x+21[/tex]
[tex]x^2-3x+7x-21=0[/tex]
[tex]x^2+4x-21=0[/tex]
Using grouping method 4x can be written as (7x-3x). Because the product of 7 and -3 is equal to the constant term -21 and the addition of 7 and -3 is equal to the coefficient of x.
[tex]x^2+7x-3x-21=0[/tex]
[tex]x(x+7)-3(x+7)=0[/tex]
[tex](x-3)(x+7)=0[/tex]
Equate each factor equal to 0.
The value of x is 3 and -7. Therefore, the option C is correct.
The extraneous solutions are x=3 or x=−7.
We have the equation; log4 (x) + log4(x - 3) = log4 (-7x + 21) we can write;
log4[x(x - 3)] = log4 (-7x + 21)
log4 can be cancelled out from both sides and we have;
x^2 - 3x = -7x + 21
To have a proper quadratic equation;
x^2 + 4x -21 = 0
The solutions of the quadratic equation therefore are x=3 or x=−7.
Learn more about quadratic equations; https://brainly.com/question/4390345